Maternal Sleep-disordered Breathing and Adverse Pregnancy Outcomes: A Systematic Review and Meta-Analysis. Issue 1 (March 2015) - Pamidi, S.; Pinto, L.M.; Marc, I.; Benedetti, A.; Schwartzman, K.; Kimoff, R.J.
Abstract : ( Am J Obstet Gynecol. 2014;210(1):52.e1–52.e14)